Cerebral blood flow modulations during antisaccade preparation in chronic hypotension. (19th November 2018) - Duschek, Stefan; Hoffmann, Alexandra; Montoro, Casandra I.; Bair, Angela; Reyes del Paso, Gustavo A.; Ettinger, Ulrich
Abstract: In addition to symptoms including fatigue, dizziness, reduced drive, or mood disturbance, individuals with chronic low blood pressure (hypotension) frequently report cognitive complaints. While attentional deficits have been empirically confirmed, it is still unknown whether the impairments also encompass executive functions. This study investigated cerebral blood flow modulations in hypotension during a precued antisaccade/prosaccade task requiring the executive function of proactive inhibition in addition to preparatory attention. Using functional transcranial Doppler sonography, bilateral blood flow velocities in the middle cerebral arteries (MCA) were recorded in 39 hypotensive and 40 normotensive participants. In the task, a stimulus appeared left or right of a fixation point 5 s after a cuing stimulus; subjects had to move their gaze to the mirror image position of the stimulus (antisaccade) or toward it (prosaccade control condition). Video‐based eye tracking was used for ocular recording. A right dominant MCA blood flow increase arose during task preparation, which was smaller in hypotensive than normotensive participants. In addition, hypotensive participants exhibited lower peak velocity of the saccadic response. The extent of the reductions in blood flow and task performance in hypotension did not differ between antisaccade and prosaccade conditions. The smaller MCA flow increase may reflect reduced activity in the dorsolateral prefrontal and inferior parietal cortices during proactive inhibition and preparatory attention in hypotension. Given that group differences in blood flow and performance arose independent of task complexity and executive function load, hypotension may be characterized by basic attentional impairments rather than particular executive function deficits.